Narrative methods for organizational and communication research / David M. Boje. - Boje, David M. (SAGE series in management research, 2001)
This work is a practical guide for researchers who need to look at alternative discourse analysis strategies. Topics covered include deconstruction analysis, microstoria analysis, story network analysis and plot analysis.